SENSORY NEURONOPATHY; A CASE REPORT AND A REVIEW OF THE ROLE OF GANGLION NERVE BIOPSY IN DIAGNOSIS. Issue 11 (9th October 2013) - Waddell, Briony; Farmer, Simon; Lunn, Mike; O'Riordan, Jonathon I
Abstract : Dorsal root ganglionopathies present with sensory ataxia, areflexia and asymmetrical positive and negative sensory phenomenon of both limb often with trigeminal involvement. There may be associated Adie's pupil 1 Despite their classical features and relatively discrete list of causes they can be difficult to definitively diagnose. We present such a case in whom biopsy of the thoracic dorsal root ganglion resulted in identifying of continued inflammation despite normal haematological makers thereby altering subsequent management. A 54 year old telecommunications officer with a background of anterior uveitis presented with a 3 year history of progressive altered sensation of his right hand and a 2 month history of altered sensation of the right side of his face including oral mucosa. There was unilateral facial sensory loss to pin prick, right upper limb pseudoathetosis, hyperaesthesia of C5 to C8 and impaired proprioception to wrist. He was hyporeflexic throughout. He was on no regular medication, was a lifelong smoker, drank minimal alcohol and denied any family history. His immunology demonstrated a positive cANCA at 7 (0–5) and positive ENA (anti–La ). He had normal inflammatory markers, vitamins B6 and B12, homocysteine, methylmalonic acid, folate, serial antineuronal antibodies, HIV, angiotensin converting enzyme, phytanic acid, protein electrophoresis, chest X–ray, contrast MRI imaging of brain, cervical spine and brachial plexus. He had 3 large volume CSF analyses with normal cell count, protein, glucose ratio, and negative oligoclonal banding and cytology. His neurophysiology was positive for a possible right sided ganglionopathy. There was an associated parathyroid adenoma which was removed. Repeat CT of chest abdomen and pelvis demonstrated a pulmonary nodule with no change noted on serial images and follow up FDG–PET at 2 years was normal. He was initially treated with IV methylprednisolone and oral taper. He also received immunoglobulin. There was further clinical deterioration so was initiated. Despite these immunosuppressive therapies he continued to clinically deteriorate with distal mild weakness, areflexia and worsening proprioceptive deficits to his left wrist and MTP joints bilaterally. Inflammatory markers were persistently normal throughout. A radial nerve biopsy demonstrated axonal loss with no evidence of active inflammation. It was therefore unclear whether his ongoing deterioration was related to neurodegeneration or ongoing inflammation. A thoracic DRG biopsy was therefore undertaken. This demonstrated florid macrophage–mediated neuropathy with frequent myelin digestion. Due to evidence of an active inflammatory process he was treated with pulsed IV cyclophosphamide to a total of 10g with stabilisation of his limb signs. He is now maintained on Azathioprine. Our case demonstrates the important information that can be gained from DRG biopsy in those with clinical deterioration despite immunosuppressive treatment. DRG is invasive, however reports demonstrate high diagnostic yield and low post–operative complication rates when thoracic ganglions are biopsied. 2